Advergame: A Case Study on Young People in Lima, Peru - Cormán-Chávez, Carla Gianinna (2024)
The new entertainment industry has led brands to link themselves strategically to the gaming sector, so they use the advergame as a format and attractive advertising action to reach their consumers. For this reason, this research answers the following question: What is the perception of young people about the components of the advergame in the KFC brand during 2022? Regarding the methodology, a qualitative phenomenological study was applied. Likewise, a case study was used as a method supported by the interview technique, with a guide validated by expert judgment. Subsequently, with the data triangulation, the information obtained was systematized. The results show that the advergame seeks to generate a bond based on the current context. Therefore, it enters spaces where advertising is not necessarily present. It also complements branding strategies since it is implemented in line with communication trends—according to the country's reality—and the user's experience.